2020
DOI: 10.33549/physiolres.934508
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Affect Male Testicular Steroidogenesis

Abstract: Through their receptors at each level of hypothalamo-pituitary-gonadal axis glucocorticoid excess, either endogenous or administered or stress-induced, could affect steroid production in the testis and thus male fertility. The main ways by which glucocorticoids act are as follows: 1) Affecting gonadoliberin and LH synthesis and release through glucocorticoid receptors in hypothalamic neurons and pituitary gonadotropes. 2) By so far not clearly evidenced reduction of the number of LH receptors on the membrane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Among these, the metabolism of purines are involved in cellular translation processes and sperm motility for generation F1 [ 50 , 51 ]. Glucocorticoids involved in steroidogenesis [ 52 ], but also in sugar metabolism, immune function and inflammatory processes, appears as a discriminant metabolite in this first generation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the metabolism of purines are involved in cellular translation processes and sperm motility for generation F1 [ 50 , 51 ]. Glucocorticoids involved in steroidogenesis [ 52 ], but also in sugar metabolism, immune function and inflammatory processes, appears as a discriminant metabolite in this first generation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glucocorticoids suppress testosterone produced by Leydig cells causing apoptosis of Leydig cells and disrupting spermatozoa maturation and motility. A study by Hampl and Starka showed that sleep deprivation increases serum glucocorticoid levels after one day, three days, and five days compared to control 14 .…”
Section: Spermatozoa Motilitymentioning
confidence: 97%
“…Adverse effects of endogenous (e.g., stress-induced) or exogenous glucocorticoid (GC) excess on male reproduction are well established in experimental as well as clinical studies. 1 Exogenous GCs are among important drugs that are administered for different indications especially as anti-inflammatory or immuno-suppressive agents in human and veterinary patients.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of endogenous (e.g., stress‐induced) or exogenous glucocorticoid (GC) excess on male reproduction are well established in experimental as well as clinical studies. 1 …”
Section: Introductionmentioning
confidence: 99%